Morphotectonic Characteristics Of Cisadane Watersshed Based On Satellite Images Analysis - Mawardi, Sonny; Sukiyah, Emi; Haryanto, Iyan (Pusat Survei Geologi, 2019)
Cisadane Watershed is one of the most rapidly growing areas and infrastructure development, and has developed as a residential, industrial, administrative centers and other economic activities. The purpose of this paper is to use remote sensing satellite imageries to identify the morphotectonic characteristics of the Cisadane watershed both qualitatively and quantitatively. Processing stereomodel, stereoplotting and stereocompilation on TerraSAR-X Digital Surface Model (DSM) and SPOT 6 imageries, produced the Digital Terrain Model (DTM) image, which has not been affected by land cover. Fusion of the DTM and Landsat 8 RGB 567+8 images is used to interpret the distribution of lithology, geomorphological units, and lineaments, which are an indication of geological structures. The morphotectonic characteristics of sub-watersheds qualitatively was carried out a bifurcation ratio calculation (Rb) which indicates tectonic deformation. Based on the analysis of satellite images both qualitatively and quantitatively, the morphotectonic characteristics of the upstream, middle and downstream Cisadane Watershed have been deformed.Keywords : satellite images, morphotectonic, DSM, DTM, Cisadane Watershed.